High-performance voltage control of ladder boost converters using robust backstepping sliding mode control - Thanh-Lam Le; Nguyen Nhan Bon (Institute of Advanced Engineering and Science, 2026)
This paper presents a control-focused solution for high-gain DC-DC conversion by integrating a capacitor-diode ladder boost converter (CDLBC) with a backstepping sliding mode control (BSMC) scheme. While the CDLBC topology provides modular voltage gain at moderate duty ratios, the core contribution lies in the development of a robust control strategy to address the converter’s nonlinear and multistage dynamics. The proposed BSMC method combines the recursive design of backstepping with the finite-time convergence and disturbance rejection properties of sliding mode control (SMC). A saturation function is employed to suppress chattering and ensure smooth control action. The controller is derived based on Lyapunov stability theory and implemented on a digital signal processor without requiring hardware modification. Experimental results under various output voltage transitions show that the BSMC approach significantly improves transient performance, reduces voltage ripple, and enhances regulation accuracy compared to conventional SMC. These findings confirm the effectiveness and practicality of software-based robust control for efficient and adaptive DC-DC power conversion in renewable energy and embedded applications.